Contemporary knowledge of typical and atypical development of verbal communication - Nadica Jovanović; Sladjana Ćalasan (Биомедицинска истраживања, 2018)
Communication can generally be defined as an exchange of messages between the sender and recipients. When analyzing the characteristics of communication, the classification into verbal and non-verbal communication is often referred to in literature. Typical child development includes the stages of pre-intentional, intentional pre-symbolic and intentional symbolic communication. Every child goes through the same phases of communication development, but the time at which he or she enters certain stage as well as its duration is not always the same for each and every child. Some children exhibit atypical development of communication. Due to this, some periods of communication development last longer compared to those children going through the stages of typical development. Communication disorders represent a serious and common problem faced by the child, parents and the wider community where the child grows up, because if there are communication difficulties at an early age, additional problems concerning insufficiently adopted speech-language system may appear. Speech and language delays recorded at an early age often appear throughout the developmental period and have negative consequences for academic achievements in school, as well as for the overall communication and social functioning of children in older age.
Keywords: verbal communication; communication development; atypical communication development